ESTIMATION OF INDUCED CURRENTS IN THE SHIELDS OF ELECTRICAL POWER CABLES WITH XLPE INSULATION - I. V. Oleksyuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
Electrical power cables with Cross-Linked Polyethylene Insulation (XLPE-insulation) are currently utilized in projects of the electric-power supply systems of modern facilities. However, the higher costs, the incomplete design, installation and maintenance normativetechnical basis as well as certain constructional features of the XLPE-insulated cable lines hinder their large-scale implementation.The cables with XLPE insulation are mostly produced in a single-conductor core version being provided with a composite copper shield whose cross-section may vary while the electric conductor cross-section remains uniform. Earthing the cable shields on both sides causes the flow of electricity in them. The course of operational service of the XLPE-insulated cable lines revealed the following fact – the currents induced in the cable shields can run up to the levels commeasurable with those in the conductor-cores themselves. That, in its turn, leads to electrical safety-level reduction, cable lines failure, and economic losses. The currents induced in the shields may occur both in symmetric (normal and emergency) and asymmetric operating modes of the power grid with values of the induced currents reaching 80 % of the conducting core currents. Many factors affect the level of the current induced in the shield: the midpoint conductor modes, the values of the core longitudinal currents in the normal and emergency operating modes, failure mode, the cross-section area of the shield, the cables mutual disposition, and the distance between them.The paper claims experimental existence conformation of the cable-shield current induced by that in the conductor-core and demonstrates its measured value. The author establishes that induction of dangerous currents in the cable shields demands elaboration of measures on reducing their level.